Actinobacteria diversity and biotechnological applications - Singh, Bhim Pratap; Gupta, Vijai Kumar; Passari, Ajit Kumar (New and future developments in microbial biotechnology and bioengineering, 2018)
Actinobacteria: Diversity and Biotechnological Applications: New and Future Developments in Microbial Biotechnology and Bioengineering, a volume in the series New and Future Developments in Microbial Biotechnology and Bioengineering series, offers the latest on the biotechnology of Kingdom actinobacteria, covering unique niches like their endosphere, rhizospheric soil and contaminated sites, etc. The book also covers the bioactive secondary metabolites obtained from actinobacteria and describes the application of microorganism (Actinobacteria) in plant growth promotion and in environmental cleanup. Finally, the book describes the biocontrol aspects of actinobacteria and how they can control fungal phytopathogens and the production of secondary metabolites